Atlantic Multidecadal Oscillation Modulates the Relation of ENSO With the Precipitation in the Central-Western Indian Ocean - Zhao, Chiyu; Geng, Xin; Qi, Li (Frontiers in Earth Science, 2022)
It is well known that the El Niño-Southern Oscillation (ENSO) could affect the precipitation anomalies in the central-western Indian Ocean (CWIP) through modifying the Walker circulation, with an El Niño generally accompanied by an enhanced CWIP. In this study, we find that this positive association is modulated by the Atlantic Multidecadal Oscillation (AMO). When ENSO and AMO are out-of-phase combinations (i.e., AMO-/El Niño and AMO+/La Niña), the CWIP is significantly stronger than that when they are in-phase cooperated. It is suggested that the AMO’s modulating effect mainly comprises two pathways that influence ENSO’s linkage with the CWIP. On one hand, AMO could modulate the SST variability in the central-eastern tropical Pacific with a stronger ENSO SST amplitude during its negative phase, thus influencing the ENSO-CWIP relationship. On the other hand, AMO is associated with a multidecadal atmospheric variation in the Walker circulation. The weakened circulation during the negative AMO phase favors an anomalous ascending flow over the central-western Indian Ocean, thereby favoring an enhanced CWIP there. Therefore, El Niño is accompanied by a more pronounced CWIP during the negative AMO phase compared to that during a positive AMO phase. For La Niña episodes, however, these two pathways have opposite modulation effects. Although AMO+/La Niña is weaker than AMO-/La Niña, the accompanied CWIP is relatively stronger as an multidecadal dry background induced by the Atlantic warming reinforces the negative CWIP anomaly generated by La Niña. We here highlight that the AMO decadal forcing needs to be considered when investigating the Indian Ocean atmospheric variabilities during ENSO events.